2014
DOI: 10.1310/hpj4909-804
|View full text |Cite
|
Sign up to set email alerts
|

Nab-Paclitaxel and Carboplatin (Nab-PC) Regimen for Advanced Non-Small-Cell Lung Cancer

Abstract: The complexity of cancer chemotherapy requires pharmacists be familiar with the complicated regimens and highly toxic agents used. This column reviews various issues related to preparation, dispensing, and administration of antineoplastic therapy, and the agents, both commercially available and investigational, used to treat malignant diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Therefore, novel treatment is needed to improve the outcomes of AWT. Currently, nab-paclitaxel plus carboplatin (Nab-PC) has been extensively studied in advanced non-small-cell lung cancer [ 16 , 17 ], breast cancer [ 18–20 ], esophageal cancer [ 21 ] and ovarian cancer [ 22 ]. A number of clinical studies showed that nab-paclitaxel and carboplatin have good effectiveness and safety.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, novel treatment is needed to improve the outcomes of AWT. Currently, nab-paclitaxel plus carboplatin (Nab-PC) has been extensively studied in advanced non-small-cell lung cancer [ 16 , 17 ], breast cancer [ 18–20 ], esophageal cancer [ 21 ] and ovarian cancer [ 22 ]. A number of clinical studies showed that nab-paclitaxel and carboplatin have good effectiveness and safety.…”
Section: Discussionmentioning
confidence: 99%